Compendium of malaysian hydrogeology research papers and reports titles - Malaysia. National Hydraulic Research Institute of Malaysia (NAHRIM) 5727; Malaysia. Kementerian Sumber Asli dan Alam Sekitar ([Putrajaya] : National Hydraulic Research Institute of Malaysia, 2008)
PSZJBL